Revision of the Papua New Guinea genus Elemacoris Miller (Hemiptera: Reduviidae: Harpactorinae) - Zhao, Ping; Constant, Jerome; Cai, Wanzhi (Zootaxa, 2007)
The species of the Papua New Guinea genus Elemacoris in the reduviid subfamily Harpactorinae are revised. Two species, E. vittatus Miller, 1958 and E. doesburgi Zhao, Constant & Cai, sp. nov., are described or redescribed, illustrated, and keyed. The diagnostic characters of the genus are modified. The type specimens of the new species are preserved in the Royal Belgian Institute of Natural Sciences.